Waste management : challenges, threats and opportunities - Singh, Rajeev Pratap; Sarkar, Abhijit (Environmental scientist) (Waste and waste management series., 2015)
Over the last couple of decades, rapid urbanization, unplanned industrialization, and a rising population jointly created several issues worldwide, particularly in developing and underdeveloped countries. One such issue that requires urgent attention is the ever-increasing waste problem which has become an exasperation for regional and local governments and an issue of both national and international importance. Waste in any form and character are the byproduct of anthropogenic activities. To move forward towards a cleaner and greener future, we need to deduce sustainable technologies - to red.